ZAMONAVIY GEOURBANISTIK TADQIQOTLARIDA “QULAYLIK INDEKSI” TUSHUNCHASI (UBS Scientific Bulletin, 2025)
In this article, the content of the concept of "Convenience index"and the use of factors determining comfort in modern geo-urban studies, the factorsaffecting the organization and development of a comfortable urban environmentare studied. In order to assess the comfort level of the Namangan city, thesociological research method was implemented using IT technologies through thedocs.google platform. In a sociological research, problems of socio-economicdevelopment of the Namangan city, which is considered the largest city of   Uzbekistan, were identified, and the representative opinions of the respondentswere studied and relevant conclusions were drawn.